Chasing secrets - Choldenko, Gennifer, 1957- (Yearling, 2016)
Thirteen-year-old Lizzie and her secret friend Noah, who is hiding in her house, plan to rescue Noah's father from the quarantined Chinatown, and save everyone they love from contracting the plague that is spreading in 1900 San Francisco.